RETRACTED: Open Nephroureterectomy Compared to Laparoscopic in Upper Urinary Tract Urothelial Carcinoma: A Meta-Analysis - Liu, Guihong; Yao, Zeqin; Chen, Guoqiang; Li, Yalang; Liang, Bing (Frontiers in Surgery, 2021)
Background: In this meta-analysis, we will focus on evaluating the effects of open nephroureterectomy compared with laparoscopic nephroureterectomy on postoperative results in upper urinary tract urothelial carcinoma subjects. Methods: A systematic literature search up to January 2021 was performed, and 36 studies included 23,013 subjects with upper urinary tract urothelial carcinoma at the start of the study; of them, 8,178 were laparoscopic nephroureterectomy, and 14,835 of them were open nephroureterectomy. They were reporting relationships between the efficacy and safety of open nephroureterectomy compared with laparoscopic nephroureterectomy in the treatment of upper urinary tract urothelial carcinoma. We calculated the odds ratio (OR) or the mean difference (MD) with 95% CIs to evaluate the efficacy and safety of open nephroureterectomy compared with laparoscopic nephroureterectomy in the treatment of upper urinary tract urothelial carcinoma using the dichotomous or continuous method with a random or fixed-effect model. Results: Laparoscopic nephroureterectomy in subjects with upper urinary tract urothelial carcinoma was significantly related to longer operation time (MD, 43.90; 95% CI, 20.91–66.90, p < 0.001), shorter hospital stay (MD, −1.71; 95% CI, −2.42 to −1.00, p < 0.001), lower blood loss (MD, −133.82; 95% CI, −220.92 to −46.73, p = 0.003), lower transfusion need (OR, 0.56; 95% CI, 0.47–0.67, p < 0.001), and lower overall complication (OR, 0.79; 95% CI, 0.70–0.90, p < 0.001) compared with open nephroureterectomy. However, no significant difference was found between laparoscopic nephroureterectomy and open nephroureterectomy in subjects with upper urinary tract urothelial carcinoma in 2–5 years recurrence-free survival (OR, 0.90; 95% CI, 0.69–1.18, p = 0.46), 2–5 years cancer-specific survival (OR, 0.94; 95% CI, 0.69–1.28, p = 0.68), and 2–5 years overall survival (OR, 1.31; 95% CI, 0.91–1.87, p = 0.15). Conclusion: Laparoscopic nephroureterectomy in subjects with upper urinary tract urothelial carcinoma may have a longer operation time, shorter hospital stay, and lower blood loss, transfusion need, and overall complication compared to open nephroureterectomy. Further studies are required to validate these findings.